Zmagania z ideologią. Pierwsza Polska Wystawa Przemysłu Lekkiego w Moskwie (1949) - Katarzyna Jeżowska (Miejsce)
In the late 1980s Andrzej Turowski, a prominent Polish art historian, coined the term ideoza. He used it to describe an obsessive situation in which every decision, both personal and institutional, had been conditioned and impelled by a currently dominated ideology. Although Turowski used this portmanteau primarily in relation to culture, in the later years many researchers claimed that every sphere of peoples’ activity under socialist regime was equally oppressed by the Party-state. In this paper I examine the 1st Exhibition of the Polish Light Industry held in Moscow in 1949. Organised in the very year of the proclamation of Socialist Realism in arts and architecture, the exhibition aimed to redefine Polish national style in the new circumstances. As unpublished archival documents reveal, the bureaucrats, tradesmen and architects involved in the preparation of the event tried to balance the need to acknowledge the ideology and employ the pragmatism of a trade exhibition. In order to understand this challenge, this paper looks up closely at the process of creating the exhibition – forming its rationale, narrative and visual side – and confronts it with (scarce) material illustrating the final outcome presented to the public.